ON THE SPECIES ASTRAGALUS AUSTROFERGANICUS KAMELIN & V.M.VINOGR. LISTED IN THE RED BOOK OF THE REPUBLIC OF UZBEKISTAN - N.G. Khoshimova; Kh.R. Khoshimov; A.R. Batoshov (Research Focus International Scientific Journal, 2025)
This study presents comprehensive data on Astragalus austroferganicus Kamelin & V.M.Vinogr., a critically rare and narrowly endemic plant species included in the Red Book of the Republic of Uzbekistan. The species, long thought to be extinct, was rediscovered during targeted fieldwork between 2020 and 2024 in the southern foothills of the Chatkal Range (Chust-Pop hills). Morphological characteristics, habitat preferences, distribution range, population size, and major threats were assessed using modern geospatial tools (Google EarthPro, ArcGIS 10.6.1) and herbarium records. The species is threatened primarily by livestock grazing and climate-induced ecological changes. This study emphasizes the importance of continuous monitoring, ex situ conservation, and the establishment of seed banks to ensure the survival of this rare taxon.